Identification of Resistant Genotype(s) of Cherry Tomato against Root-knot Nematode under Controlled Epiphytotic Conditions (Indian Journal of Nematology, 2025)
Root-knot nematode, Meloidogyne incognita is a major problem in cherry tomatoes, that is very prominent in protected cultivation. Sixty-three cherry tomato genotypes were screened in pots under protected conditions to identify resistant genotypes against root-knot nematode along with resistant and susceptible checks. The experiment took place at Vegetable Research Farm, PAU, Ludhiana during 2021–2022 and 2022–2023. The genotypes, grown in the pots, were inoculated with second-stage juveniles of root-knot nematode; a similar set of genotypes was grown in pots with uninoculated soil. The plants were allowed to grow for 90 days and then uprooted to study the root characters, symptoms and comparison. The genotypes PCT-42, PCT-13 and PCT-27 exhibited the resistant reaction (Resistant reaction-2) and showed less development of root-knots in inoculated pots. Genotypes PCT-12, PCT-18, PCT-21, PCT-25, PCT-33, PCT-34, PCT-35, PCT-46, PCT-47, PCT-49 and PCT-59 exhibited a moderately resistant reaction (Resistant reaction-3) against root-knot nematodes. While comparing healthy and infected plants, it was found that the infected plants exhibited retarded growth, shorter root length and lower root weight. The average height difference between infected and healthy plants was 6.90 cm, with a maximum variation of 39.18 cm. Additionally, the average differences in root weight and root length were 1.25 g and 2.36 cm, respectively. This understanding enhances our comprehension of how cherry tomatoes respond to root-knot nematodes. The identified resistant genotypes can be utilized in future breeding efforts to introduce resistance into desirable varieties.